ANALISIS KINERJA UMKM BERDASARKAN TINGKAT PENDIDIKAN, PENGETAHUAN AKUNTANSI DAN PENGGUNAAN INFORMASI AKUNTANSI - Mulyani, Hani Sri; Dadang Sudirno; Endah Prihartini; Sari Toyibah (Program Studi Akuntansi Fakultas Ekonomika dan Bisnis Universitas Majalengka, 2025)
Micro, Small and Medium Enterprises (MSMEs) are very important for the Indonesian economy, creating jobs and supporting during the economic crisis. The contribution of MSMEs will reach 61.09% of GDP in 2022 and absorb a lot of workers. In Majalengka Regency, MSMEs are very important during the COVID-19 pandemic even though economic growth has not been achieved due to lack of knowledge and poor management. Therefore, this research aims to find out how the level of education, accounting knowledge and use of accounting information partially influence the performance of MSMEs in Majalengka sub-district. The method used in this research is a quantitative research method with a descriptive and verification analysis approach. The population in this study was 315 Micro, Small and Medium Enterprises (MSMEs) in Majalengka District. The sample used in this research used a nonprobability sampling technique with a purposive sampling method, resulting in a sample of 160 Micro, Small and Medium Enterprises (MSMEs) in Majalengka district. The data analysis used was multiple linear regression analysis with the help of the SPSS version 25 program. The results of this research show thatl thel level ofl educationl hasl al significant effect on the performance of MSMEs, accounting knowledge has a significant effect on the performance of MSMEs, the use of accounting information has a significant effect on the performance of MSMEs.